Studying the Effect of Competitive Intelligence on Organizational Performance in Commercial Banks: A Survey on Commercial Banks - Sonia Sarami; Asadollah Kordnaeich; Asghar Moishabaki Esfahani (Journal of Information Technology Management)
The importance of obtaining market information via organization’s competitive intelligence considering the extensive changes which companies are experiencing in different areas like increased pressure of competition, emerging new technologies, privatisation in thier competitive environment is now more than ever and can highly affect organizational performance. Hence this study assessed the effect of competitive intelligence on organizational performance in commercial banks. This research was an applied research in terms of purpose and correlational descriptive in terms of data gathering method. The statistical population of the study is the 22 commercial banks that 14 banks cooperated with this research and from the cooperating banks we gathered a sample of 174 participants. Data were gathered by questionnaire and At the end, by using Structural equation modeling and SmartPLS and SPSS softwares hypothesis were tested. Research findings showed that competitive intelligence affects organizational performance.Its indicators which are, competitors,technologic, strategic-social and market intelligence also affect organizational performance respectively.